Legal Protection For Civil Servants Against The Annulment Of The Dishonorable Dismissal Beschikking (In Decisions Number: 19/G/2013/PTUN-BL, 156/G/2016/PTUN-MDN, 43/G/2019/PTUN-SRG) - Juliannoor, Giovanni Dion Pratama; Prasetyo, Bayu (Fakultas Hukum Dehasen, 2025)
This research aims to analyse the form of legal protection given to civil servants over the cancellation of the dishonourable dismissal (PTDH) beschikking in a state administrative court decision. PTDH is often an important issue in the context of personnel administration, given its significant impact on the career and administrative rights of civil servants. This research uses normative legal methods with conceptual and case study approaches, and analyses various laws and regulations, legal doctrines, and general principles of good governance (AUPB). The results show that judges have a crucial role in ensuring that PTDH decisions fulfil fair and procedural legal principles. In decisions Number: 19/G/2013/PTUN-BL, Number: 156/G/2016/PTUN-MDN, and Number: 43/G/2019/PTUN.SRG, various violations related to procedure, authority, and substance were found that caused the PTDH decision to be declared invalid. However, in some cases, rehabilitation of civil servants is not fully granted, given the limited evidence or insufficiently strong legal reasons. This research emphasises the importance of applying the principles of justice, legal certainty, and protection of civil servants' rights in the civil service administration process. In addition, this research provides recommendations to improve regulations related to the dismissal of civil servants to be more consistent with applicable legal principles.